(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The research aims to determine the effectiveness of auditing in light of the relationship between the governance of investment policy and the cost of debt in companies listed on the Iraqi Stock Exchange. The problem of the research is to raise the question about the effect of the governance of investment policy and the cost of debt on the effectiveness of auditing and auditors. During the research, the most important of them were: the existence of an impact relationship on the effectiveness of auditing through the relationship between the governance of investment policy and the cost of debt. The companies listed in the Iraqi Stock Exchange lack an effective proposed guide or framework dealing with the governance of investment policy despite the presence of laws and regulations to protect investors and shareholders, but they did not It is applied if it may affect the desire of stakeholders to invest in these companies. The most important recommendations reached by the research were: Urging the application of the mechanisms and principles of corporate governance and the governance of investment policy by working to educate the community about it, and that its application is considered a safety against conflict of interest and fraud and protection their interests, and also recommended the necessity of forming specialized committees with expertise to formulate principles for the governance of investment policy that suit the Iraqi environment In accordance with the principles issued by the OECD Development Organization, and preparing a guide or a proposed audit framework that includes the principles of governance and the governance of investment policy or the cost of borrowing, including the audit procedures that the auditor must perform to ensure the application of governance and its impact on the continuity of work in the economic unit.